Pemahaman Siswa Madrasah Ibtidaiyah Ihya Ulumiddin Banjarmasin terhadap Reaksi Asam Basa melalui Percobaan Asam Cuka dan Soda Kue - Gusti Hadiatus Solehah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to examine the understanding of students at Madrasah Ibtidaiyah Ihya Ulumiddin Banjarmasin regarding acid-base reactions through experiments using simple materials, namely vinegar and baking soda. The method used is qualitative research with a case study approach, where data is collected through observation, interviews, and documentation during the experiment. This research involves a number of fourth-grade students as research subjects. The results show that most students understand the basic concepts of acid-base reactions, such as color changes and gas bubble formation, although there are still some difficulties in explaining the relationship between reactants scientifically. This study provides an overview of the potential and challenges in teaching basic chemistry concepts at the Madrasah Ibtidaiyah level, and suggests a more interactive learning approach to enhance student understanding.